4(x+3)-9=x+3(x+1)

Simple and best practice solution for 4(x+3)-9=x+3(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+3)-9=x+3(x+1) equation:



4(x+3)-9=x+3(x+1)
We move all terms to the left:
4(x+3)-9-(x+3(x+1))=0
We multiply parentheses
4x-(x+3(x+1))+12-9=0
We calculate terms in parentheses: -(x+3(x+1)), so:
x+3(x+1)
We multiply parentheses
x+3x+3
We add all the numbers together, and all the variables
4x+3
Back to the equation:
-(4x+3)
We add all the numbers together, and all the variables
4x-(4x+3)+3=0
We get rid of parentheses
4x-4x-3+3=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 2(5x+3x)=64 | | −9g−12=−6g−39 | | 120+20b=180 | | -60=6+14k | | 4-6n=-5n | | 6(x-3)=8(x-4 | | 5(x-4)/2=15 | | 850=1.5x+x | | 2x^-1-11x^-1-6=0 | | 20-4x=40-12x | | 2w-12=4w | | 8n+1=6n+27 | | 3/x-4=2 | | 7r=8+6r | | 14v=9v+10 | | N-70=-(15x4) | | 8+1.20r=29.60 | | 3x+5x+42=99 | | -10+2x=20-4x | | 3-6g=-7+g | | 3(y-1)=2(9+y) | | 6x+9+3x-4=32 | | 2x+3x-3=3 | | 5x+5=4x+31 | | 9x-2x+60=9x+36 | | 2x-95=73-4x | | 9y-7=2 | | -4x+7=36 | | 1+4x+4x=17 | | 9x-2x+20=9x=36 | | 15+8x=9x+7 | | -3(r+4)=44 |

Equations solver categories